Da'wah Communication Of Qasidah Group 'Nasida Ria' In The Digital Age - Zulfikar Ikrom; Dindin Dimyati (Universiti Sains Islam Malaysia, 2025)
Al-i’lam - Journal of Contemporary Islamic Communication and Media, Volume 5 Issue 1 Page (18-34)